Isolation and Identification of Marine Algae (Oscillatoria Sp.) From Kuantan Coastal Region Malaysia and Studies on Their Bioactive and Antibacterial Properties - Rofiza, Mansor; Norafattull Salwa , Ab Rahman; Siti Fatimah, Mohamad; Kuppusamy, Palaniselvam; M. M., Yusoff; Natanamurugaraj, Govindan (IDOSI Publication, 2013)
Marine algae is an incredible group of prokaryotic organisms that produce a variety of industrially and clinically important secondary metabolites. In this study explore the marine cyanobacteria (Oscillatoria Sp.) was isolated from the Kuantan coastal area and on their anti-microbial activity and bioactive compounds. The ethanolic Oscillatoria Sp. extract was subjected to GC-MS analysis to determine the bioactive compounds. Also the ethanolic extract used for antibacterial activity by disk diffusion assay using four different types of pathogenic bacteria such as P. aurogenosa, Bacillus subtilis, Staphylococcus aureus and Escherichia coli. The zone of inhibition was observed and measured in the experimental petri plates. The antibacterial activity showed that the ethanol extract of Oscillatoria Sp. was effective against P. aeruginosa the 16mmzone of inhibition was observed. The microalgae crude extract was highly significant in against tested gram-positive bacteria. Moreover, GC-MS analysis data shows the present of several compounds such as phenol derivatives and fatty acid derivatives in the sample. The compounds are mainly responsible for controlling the gram positive bacteria.